1999
DOI: 10.1111/j.1572-0241.1999.983_f.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Antiendomysium and Antigliadin Antibodies in Untreated Celiac Disease: Disappointing in Clinical Practice

Abstract: Interpretation of negative serology needs great awareness. Although EMA sensitivity in total villous atrophy is excellent, in partial villous atrophy the sensitivity of EMA appears to be disappointing. Our experience shows that EMA and AGA have only limited value in screening programs for CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
2
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(107 citation statements)
references
References 26 publications
1
92
2
5
Order By: Relevance
“…Histopathology was expressed according to the Marsh modified classification [13,14]. For the cutoff for intraepithelial lymphocytes, we used 25/100 according to Hayat et al [15] and Dickson et al [16].…”
Section: Histological Classificationmentioning
confidence: 99%
“…Histopathology was expressed according to the Marsh modified classification [13,14]. For the cutoff for intraepithelial lymphocytes, we used 25/100 according to Hayat et al [15] and Dickson et al [16].…”
Section: Histological Classificationmentioning
confidence: 99%
“…These antibodies may be present in inflammatory bowel disease [97], collagen vascular disease [98] and in many healthy people [99]. However, combining AGAs, with other serologic tests increases the sensitivity of the serologic tests [100], thus increasing the overall detection rate of CD.…”
Section: Diagnosis Of CDmentioning
confidence: 99%
“…The finding that most IgA-EmA and anti-tTG IgA-negative patients were under 2 years of age is in agreement with previous reports [9, 38, 39], and could explain the relatively low frequency of these antibodies in this study. Some recent studies have questioned the high sensitivity of IgA-EmA for the whole spectrum of CoD [40, 41], and it has been shown that IgA-EmA testing fails to identify one fifth of patients, even among those with subtotal villous atrophy [41]. In this regard the significance of anti-cytoskeletal IgA antibodies as supplementary serologic markers for CoD should be further studied, as well as their association with the degree of intestinal tissue rearrangements in CoD.…”
Section: Discussionmentioning
confidence: 99%